Historical Nostalgia and Destination Loyalty Intention: Mediating Role of Perceived Value and Satisfaction among Visitors of Cultural Heritage Sites of Nepal - Satyal, Sajina; Subedi, Gopal; Pokhrel, Laxman (Journal of Business and Management, 2023)
Background: Heritage sites of Nepal are the center of attraction for national and international visitors. It is essential to delve into the factors that drive visitors to these destinations, which are influenced by the narratives and cultural significance associated with Nepal’s heritage sites. Objective: The purpose of this paper is to examine the mediating role of Perceived Value (PV) and Satisfaction (SAT) in the relationship between Historical Nostalgia (HN) and Destination Loyalty Intention (DLI) among visitors of cultural heritage sites of Nepal. Methods: The research applied a cross-sectional survey research design to collect data from 256 domestic tourists. The purposive sampling method was used to reach the respondents. Partial Least Squares Structural Equation (PLS-SEM) was applied to test hypotheses. Results: The paper findings showed that perceived values do not mediate the relationship between historical nostalgia and destination loyalty intention but show a direct effect between historical nostalgia and destination loyalty intention whereas satisfaction displays the role of mediation between historical nostalgia and destination loyalty intention. Further, historical nostalgia positively influences perceived value and satisfaction, leading to increased destination loyalty intention. Moreover, the impact of perceived value on destination loyalty intention was not supported. Conclusions: This paper can help destination managers design marketing strategies to evoke historic nostalgia and improve visitor experiences at Nepal’s heritage sites. The tourism board can apply the findings to enhance destination loyalty and increase the tourism revenue of Nepal.